Interdisciplinary management of skull base surgery - R. Rothweiler; M.C. Metzger; P.J. Voss; J. Beck; R. Schmelzeisen (Journal of Oral Biology and Craniofacial Research)
Skull base surgery remains one of the challenging areas in the field of cranio-maxillofacial surgery, otolaryngology and neurosurgery. Subsequent reconstruction of bone and soft tissue are an essential component to restore function and appearance after ablative surgery.Establishment of interdisciplinary tumor boards with presentation of the individual patient cases have become standard. Multiplanar reconstruction using MRI or CT imaging techniques combined with virtual 3D planning allow precise planning of the procedures. Intraoperative navigation helps for complete resection of malignant findings with safety margins; surgical approaches provide a good overview of the surgical site. Reconstruction using local flaps have a low complication rate with equally reliable results in reconstruction of small tissue defects. Free flap surgery makes reconstruction of large tissue defects possible. Alloplastic materials are alternatively used for reconstruction of bone defects.Based on selected patients, treatment algorithms and standard surgical procedures in extracerebral skull base surgery will be illustrated. Current techniques and new approaches will be discussed with emphasize on hard and soft tissue reconstruction.